白色念珠菌与口腔常见致病菌交互作用的研究进展 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2019)
Increasing numbers of microbiome studies have enabled the development of a greater understanding of how antagonistic and synergetic microbial interactions inﬂuence disease outcomes. Candida albicans is an opportunistic pathogen that is commonly found in human oral microﬂora. In a healthy oral environment, Candida albicans may potentially but significantly influence the balance between the oral bacterial ecosystem and the host, leading tooral diseases. The aim of this study is to review the correlation between Candida albicans and oral pathogens and provide a deeper understanding of the nature of oral infectious diseases.